2018
DOI: 10.1080/08941939.2018.1468944
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Learning Curve in Laparoscopic Inguinal Hernia Repair by Tapp: A Quality Improvement Study

Abstract: Our evaluation shows that both trainees fully completed their learning curves for the TAPP after 65 procedures, providing us with a parameter which can be taken into consideration when establishing the minimum volume necessary to guarantee correct training in laparoscopic inguinal hernia repair by a TAPP technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
3
33
0
1
Order By: Relevance
“…Previous study indicated that more than 100 endoscopic repairs are required to achieve outcomes comparable to open anterior mesh repair [ 5 ]. However, in-line with our results, other articles referred to 65 procedures as a minimum volume necessary to train for endoscopic inguinal hernia repairs [ 30 , 31 ]. Due to this discrepancy between the numbers estimated for proficiency by our surgical residents and the numbers needed for proficiency, the question arises whether surgical residents overestimate themselves, or the trainees underestimate the residents.…”
Section: Discussionsupporting
confidence: 84%
“…Previous study indicated that more than 100 endoscopic repairs are required to achieve outcomes comparable to open anterior mesh repair [ 5 ]. However, in-line with our results, other articles referred to 65 procedures as a minimum volume necessary to train for endoscopic inguinal hernia repairs [ 30 , 31 ]. Due to this discrepancy between the numbers estimated for proficiency by our surgical residents and the numbers needed for proficiency, the question arises whether surgical residents overestimate themselves, or the trainees underestimate the residents.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, during the learning curve there is a higher recurrence rates for surgeons until they reach mastery [8,51,52]. Bracale et al [53] published a study comparing 100 TAPP procedures by two different trainees and a senior surgeon. Two tests were used to evaluate completion of the learning curve: The Cumulative Sum (CUSUM) and KPSS tests.…”
Section: Surgeon's Learning Curve Case Load Experience and Frustratmentioning
confidence: 99%
“…The plateau of the LC for both laparoscopic TAPP and TEP procedures varies between 13 and 65 cases. 6,[14][15][16][17] The European Hernia Society guidelines state that the TAPP and totally extra peritoneal inguinal hernia repair LCs peak after experiencing 50-100 cases, with the first 30-50 cases having the highest incidence of complications. 18 Bansal et al reported that the average number for stabilization of the LC was 13 operations for laparoscopic TEP and TAPP.…”
Section: Discussionmentioning
confidence: 99%